Shadows in the spotlight: Navigating organizational transparency in digital contexts - Oana Brindusa Albu; Lars Thøger Christensen (Schmalenbach Journal of Business Research (SBUR), 2024)
This article examines the potential implications of pursuing organizational transparency ideals in contemporary datafied societies, i.e., societies where multiple aspects of social life take the shape of digital data. The article develops a~communication perspective of transparency which is valuable because it not only considers transparency as a~matter of providing and accessing information about already existing practices but conceptualizes transparency as a~performative practice with the potential to shape subjects, relations, and forms of organizing. The article identifies common trends in extant research on transparency, discusses different ways of thinking about transparency, and examines their implications for organizational settings. Taken together, the article problematizes predominant tendencies that theorize transparency simply from an informational standpoint, (i.e., as information disclosure) and identifies key challenges specific to digitally driven transparency. The article ends by discussing some implications of digitally driven transparency practices and sketches future research directions for organizations that face transparency challenges in the current social contexts where data is abundant.
Keywords: 650; Digitalization; Performativity; Transparency